2013
DOI: 10.1007/s10995-013-1275-0
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Cytomegalovirus Reference Material: A Content Analysis of Coverage and Accuracy

Abstract: Congenital cytomegalovirus (CMV) is the leading cause of birth defects and developmental delays in the United States. However, only 13–22 % of women in the United States have heard of CMV. This research assessed (1) the quantity and accuracy of CMV information included on pregnancy-related websites and reference books, and (2) whether CMV information was included less often than information about other birth defects or infections. A content analysis of 37 pregnancy reference books and seven websites was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…In addition, programs are not required to teach students about cCMV, specifically. A study of CMV information contained in books and pregnancy websites, demonstrated that these sources contain accurate, but not adequate CMV information [ 76 ]. CMV prevention was included in such references only 50% the time.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, programs are not required to teach students about cCMV, specifically. A study of CMV information contained in books and pregnancy websites, demonstrated that these sources contain accurate, but not adequate CMV information [ 76 ]. CMV prevention was included in such references only 50% the time.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some authors have reported a paucity of CMV information in pregnancy-related reference books and websites [ 23 , 24 ]. This aspect should be investigated in more depth in future Italian studies.…”
Section: Discussionmentioning
confidence: 99%
“…Public health communication campaigns in addition to provider counseling could be useful. In addition, ensuring that CMV information is available on pregnancy websites and reference books is important ( Thackeray et al, 2014 ). Further research regarding best practices for how to frame and communicate CMV prevention messages, particularly about the efficacy of these behaviors to reduce risk, and the most effective methods for delivering this information in healthcare and public health settings is needed.…”
Section: Discussionmentioning
confidence: 99%